Inspirasi Konstruksi Dakwah bi al-Hal KH. Abdul Ghofur Lamongan Jawa Timur - Mohammad Rofiq (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2024)
This article discusses the application of the bil al-hal da'wah construction by KH. Abdul Ghofur from Lamongan, East Java, which emphasizes the implementation of concrete actions in da'wah. This da'wah construction, meaning